Aerobactin Seems To Be a Promising Marker Compared With Unstable RmpA2 for the Identification of Hypervirulent Carbapenem-Resistant Klebsiella pneumoniae: In Silico and In Vitro Evidence - Shankar, Chaitra; Basu, Soumya; Lal, Binesh; Shanmugam, Sathiya; Vasudevan, Karthick; Mathur, Purva; Ramaiah, Sudha; Anbarasu, Anand; Veeraraghavan, Balaji (Frontiers in Cellular and Infection Microbiology, 2021)
Background The incidence of hypervirulent (hv) carbapenem-resistant (CR) Klebsiella pneumoniae (Kp) is increasing globally among various clones and is also responsible for nosocomial infections. The CR-hvKp is formed by the uptake of a virulence plasmid by endemic high-risk clones or by the uptake of plasmids carrying antimicrobial resistance genes by the virulent clones. Here, we describe CR-hvKp from India belonging to high-risk clones that have acquired a virulence plasmid and are phenotypically unidentified due to lack of hypermucoviscosity. Methods Twenty-seven CRKp isolates were identified to possess rmpA2 by whole-genome sequencing; and resistance and virulence determinants were characterized. By in silico protein modeling (and validation), protein backbone stability analysis, and coarse dynamics study, the fitness of RmpA, RmpA2, and aerobactin-associated proteins-IucA and IutA, were determined to establish a reliable marker for clinical identification of CR-hvKp. Results The CR-hvKp belonged to multidrug-resistant (MDR) high-risk clones such as CG11, CG43, ST15, and ST231 and carried OXA-232 as the predominant carbapenemase followed by NDM. The virulence plasmid belonged to IncHI1B replicon type and carried frameshifted and truncated rmpA and rmpA2. This resulted in a lack of hypermucoviscous phenotype. However, functional aerobactin was expressed in all high-risk clones. In silico analysis portrayed that IucA and IutA were more stable than classical RmpA. Furthermore, IucA and IutA had lower conformational fluctuations in the functional domains than the non-functional RmpA2, which increases the fitness cost of the latter for its maintenance and expression among CR-hvKp. Hence, RmpA and RmpA2 are likely to be lost among CR-hvKp owing to the increased fitness cost while coding for essential antimicrobial resistance and virulence factors. Conclusion Increasing incidence of convergence of AMR and virulence is observed among K. pneumoniae globally, which warrants the need for reliable markers for identifying CR-hvKp. The presence of non-functional RmpA2 among high-risk clones highlights the significance of molecular identification of CR-hvKp. The negative string test due to non-functional RmpA2 among CR-hvKp isolates challenges phenotypic screening and faster identification of this pathotype. This can potentially be counteracted by projecting aerobactin as a stable, constitutively expressed, and functional marker for rapidly evolving CR-hvKp.